Nilai-nilai Akhlaqul Karimah dalam Kitab Akhlaqul Lil Banin untuk Membentuk Karakter Sosial Santri di Pondok Pesantren Al-Fitroh - HADI, MOH SYAIKHOL; JOKO SUSILO, MOHAMAD (INNOVASI : JURNAL INOVASI PENDIDIKAN, 2025)
This study aims to determine the values of akhlaqul karimah contained in the Book of Akhlaqul Lil Banin and its implementation in the formation of social character of students at Al-Fitroh Islamic Boarding School. This book contains moral teachings which include morals to Allah SWT, Rasulullah SAW, parents, teachers, peers, and the surrounding environment. Through a descriptive qualitative approach, this study found that these values are applied through various religious and social activities in the pesantren, such as congregational prayers, book recitation, and interaction between students and ustadz. However, the application of these values is not optimal because there are still challenges in the form of the dominance of the theoretical approach, the negative influence of social media, and the lack of contextual teaching that relates the book material to the reality of santri's lives. Therefore, strengthening strategies such as teacher training, integration of practice-based learning, and revitalization of the role of pesantren as holistic character builders are needed. This research confirms that Kitab Akhlaqul Lil Banin has great potential as a relevant moral education instrument in answering the character challenges of the younger generation in the modern era.